OS3.2 Relevant topics for brain tumor patients in the Distress Thermometer, first results of the HEAT study. (6th September 2019) - Renovanz, M; Coburger, J; Tabatabai, G; Ringel, F; Wirtz, C; Mehdorn, M; Goebel, S
Abstract: BACKGROUND: Patient-centered assessments and disease-adjusted patient-reported outcome measures (PROMs) are crucial in neuro-oncology. The Distress Thermometer (DT) is a well-accepted screening tool for cancer patients including a numerical rating scale (1–10, cut-offs indicating relevant distress ≥4–6) and 40 items describing possible problem categories (emotional, social, physical, practical and spiritual). The aims of the first part of the "Adaption of the Distress T h ermom e ter in patients with intr a cranial t umors" (HEAT) study were to evaluate the importance and relevance of items for brain tumor patients (BTP). MATERIAL AND METHODS: The multicenter study included three University hospitals. After given informed consent patients were prospectively evaluated either during their hospital stay or in the outpatient setting using DT as well as the 40 item problem list. Clinical and demographic data were recorded. We performed an analysis regarding frequency of indicated topics and evaluated their relevance for patients' psychosocial well-beings via Pearson correlations with the DT score. RESULTS: Data of n = 670 patients were analyzed. Mean age was 52 years (SD = 14, range 18–81), most of the patients harbored WHO°I tumors (37%) and WHO°IV tumors (28%). Male to female ratio was 1:1, 17% were assessed preoperatively, 40% postoperatively and 43% during adjuvant therapy or follow-up. 14% of the patients faced a tumor recurrence at assessment. Mean score of DT was 5.23 (SD = 2.9, range 0–10). Applying a cut-off score ≥ 4, 61% reported distress (≥ 5: 46% and ≥ 6: 37%). Regarding the relevance of the problem list for BTP, emotional problems (e. g., anxiety, depression) were most frequently reported. A total of 14/40 (35 %) of items were endorsed by less than 10% of patients. With exception of emotional problems all areas were reflected: practical problems (e. g., problems with child care or insurance), social problems (e. g., problems with children), spiritual concerns (e. g., loss of faith), and physical problems (e. g., breathing, fever). However, some of these rarely reported problems were of relevance for patients' psychosocial well-being as indicated by significant correlations between the respective item and the DT score. This was, for example, the case for problems with childcare (r = .106; p < .01) or breathing (r = .125; p = .001). CONCLUSION: Tools developed for cancer patients do not yet perfectly reflect all needs of BTP. Based on our data, we suggest further adjustments of available tools. Yet, it should be taken into account that subgroups of BTP may require different problem lists in the DT, as we observed some topics (e.g. breathing) probably be related to BTP under chemotherapy or steroids only. Moreover, our data require cross-cultural validation as especially results regarding practical problems and insurance might differ in cultures with different social security systems.